The Influence of the Student Team Achievement Division Type Cooperative Learning Model on Critical Thinking and Learning Outcomes for Students in Indonesian Language Subjects at Madrasah Ibtidaiah Wahid Hasyim-Puger - NUR, AZIZAH (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
There are many problems when learning Indonesian.These include students who take Indonesian language classes for granted, students who consider Indonesian language classes to be boring, and tudents who do not want to actively participate in learning activities.They tend to be dominated by the teacher's explanation of the content.One of her learning models is the Student Team Achievement Division coperative Learning Model. was chosen because it provides opportunities for students to actively participate in learning, allows them to gain direct experience in discovering concepts from the content they have learned, and allows them to think critically. Because it is based on ideas. concluded study uses causal research methods to examine the relationships of variables to the objects under study. Therefore, there are independent/free (X) and dependent/constrained (Y) variables in this study. The population of this study, which used a pre-test, post-test design, consisted of his 60 students from MI Wahid Hashim Jember Indonesia. The